Impact of nano sized SiC and Gr on mechanical properties of aerospace grade Al7075 composites - M. Ravikumar; Rudra Nail (Fracture and Structural Integrity)
Aluminum composites exhibit high resistance to wear and corrosion, possess high strength, offer durability and more such properties. In this study, Al7075, reinforced with nano size SiC - Gr was produced by a stir casting technique and its microstructure and mechanical behavior were evaluated. Reinforcements were added in the range of 0 - 3 wt. %. The microstructure study, tensile and compression strength of the developed hybrid Metal Matrix Composites have been analyzed and examined. From the investigational study, it was found that the reinforcements are evenly dispersed in the base material. The porosity and density of the developed composites were found to be enhanced. The mechanical properties such as ultimate tensile and compressive strength of the developed MMCs could be improved by addition of SiC particulates compared to base material. Further, the strength of developed hybrid composites was found to be decreased by adding of solid lubricant such as graphite (Gr) particulates along with hard ceramic particulates. Finally, fractured surface of the tensile test specimens were analysed using a SEM analysis.